Taxonomic and geographic variation of the Pinus mugo complex on chloroplast microsatellite markers. Issue 5 (3rd September 2017) - Dzialuk, Artur; Boratyńska, Krystyna; Romo, Angel; Boratyński, Adam
Abstract : The high mountain plants of Central and Southern Europe survived the glacial periods in the same mountain ridges, but at lower altitudes and possibly covering larger areas than during interglacials. This implies a high level of species differentiation between isolated mountain ridges. Pinus mugo complex, which includes P. mugo s.s. (Alps, Sudetes, Carpathians, Dynaric Alps, and Rhodopes), P. uncinata (Pyrenees and Alps), and P. uliginosa (Sudetes and neighbouring mountain ridges) is a good group to examine such a scenario. We screened 44 populations across the geographic range of the complex, using 10 cpSSR markers to study (1) taxonomic relations among P. mugo s.s., P. uncinata, and P. uliginosa and (2) genetic and phylogeographic structure in P. mugo s.s. and P. uncinata . Allelic combinations of 87 size variants produced a total of 757 haplotypes. Haplotypic diversity was high and similar in every species (0.997, 0.986 and 0.991, respectively). The highest divergence between haplotypes was observed in P. uliginosa ( = 10.29). The AMOVA revealed that most of the overall genetic variation is explained by the within-population component ( FST = 0.121, RST = 0.206) and by the geography ( FCT = 0.056, RCT = 0.083). The differentiation between P. mugo s.s ., P. uncinata, and P. uliginosa is explained by about 5% ( P <0.001) of the total variation. Vicariant gene pools for the complex were identified in the Pyrenees, the Alps with the Tatra Mts, the Sudetes, and the East and South Carpathians along with the Balkan Mountains. The phylogeographic structure was observed in P. mugo s.l., P. mugo s.s., and P. uncinata. Results support the separate taxonomic status of P. uncinata and P. mugo s.s. and possible hybrid origin of P. uliginosa .